OP0074 TOFACITINIB PROMOTES FUNDAMENTAL PROCESSES OF BONE HEALING. (June 2019) - Gaber, Timo; Brinkman, Antonia; Damerau, Alexandra; Pfeiffenberger, Moritz; Ehlers, Lisa; Buttgereit, Frank; Hoff, Paula
Abstract : Background: Inflammatory diseases like rheumatoid arthritis (RA) and anti-inflammatory treatment of RA with glucocorticoids (GC) or NSAIDS negatively influence bone metabolism and fracture healing. Janus kinase (Jak) inhibition with tofacitinib has been demonstrated as a potent anti-inflammatory therapeutic agent in the treatment of RA but its impact on the fundamental processes of bone regeneration such as recruitment of human mesenchymal stromal cells (hMSCs) and chondrogenesis, osteogenesis and osteoclastogenesis is still controversial and in part elusive. Objectives: Therefore, in this study, we aim to examine the effects of Tofacitinib on processes of bone healing under reduced oxygen availability mimicking the in vivo situation of the fracture gap. Methods: To this end, we analyzed the influence of Tofacitinib on the (i) invasion of hMSCs towards TNFα using a trans-well assay, (ii) chondrogenic differentiation of hMSCs in a 3D-micro-mass culture under hypoxic conditions, (iii) osteogenic differentiation of hMSCs, (iv) M-CSF/RANKL-mediated differentiation of isolated monocytes towards osteoclasts and (v) hypoxia-mediated target gene expression in non-differentiated, osteogenic and chondrogenic differentiated hMSCs. Results: We demonstrate that Tofacitinib dose-dependently promotes the recruitment of hMSCs under hypoxia but inhibits recruitment of hMSCs under normoxia. With regard to the chondrogenic differentiation of hMSCs, we observed that Tofacitinib did not inhibit survival and at therapeutic relevant doses of 10-100nM. Moreover, Tofacitinib dose-dependently enhances osteogenic differentiation of hMSCs and reduces osteoclast survival and differentiation under hypoxic conditions. We show that Tofacitinib does not affect chondrogenic HIF target gene expression but increases HIF target gene expression in human osteogenic differentiated MSCs. Conclusion: We conclude from our data, that Tofacitinib may influence bone healing by promotion MSC recruitment into the hypoxic microenvironment of the fracture gap, does not interfere with the cartilaginous phase of the soft callus phase of fracture healing process. We assume that Tofacitinib may promote bone formation and reduce bone resorption which could in part explain the positive impact on bone erosions by Tofacitinib. Thus, we hypothesize that it will be unnecessary to stop this medication in case of fracture and suggest that positive effects on osteoporosis are likely. Acknowledgement: Funded by an unrestricted grant provided by Pfizer. Disclosure of Interests: Timo Gaber Grant/research support from: Pfizer, Antonia Brinkman: None declared, Alexandra Damerau: None declared, Moritz Pfeiffenberger: None declared, Lisa Ehlers: None declared, Frank Buttgereit: None declared, Paula Hoff Grant/research support from: Pfizer